2017
DOI: 10.1175/jpo-d-16-0167.1
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and Energetics of Trapped Diurnal Internal Kelvin Waves around a Midlatitude Island

Abstract: The generation of trapped and radiating internal tides around Izu-Oshima Island located off Sagami Bay, Japan, is investigated using the three-dimensional Stanford Unstructured Nonhydrostatic Terrain-following Adaptive Navier–Stokes Simulator (SUNTANS) that is validated with observations of isotherm displacements in shallow water. The model is forced by barotropic tides, which generate strong baroclinic internal tides in the study region. Model results showed that when diurnal K1 barotropic tides dominate, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 51 publications
3
34
0
1
Order By: Relevance
“…In addition, this area is known as an important area for maintaining marine ecosystems in the Northwest Pacific Ocean, because of strong mass transport and mixing over the shallow ridge (e.g., Hasegawa et al, ). Masunaga, Fringer, et al () reported that tidal flows induce highly nonlinear internal tides in this area. It has also been reported that the intensity of internal tides over the ridge is much higher than it is along the Japanese mainland (Masunaga, Fringer, et al, ; Varlamov et al, ).…”
Section: Introductionmentioning
confidence: 83%
See 4 more Smart Citations
“…In addition, this area is known as an important area for maintaining marine ecosystems in the Northwest Pacific Ocean, because of strong mass transport and mixing over the shallow ridge (e.g., Hasegawa et al, ). Masunaga, Fringer, et al () reported that tidal flows induce highly nonlinear internal tides in this area. It has also been reported that the intensity of internal tides over the ridge is much higher than it is along the Japanese mainland (Masunaga, Fringer, et al, ; Varlamov et al, ).…”
Section: Introductionmentioning
confidence: 83%
“…Masunaga, Fringer, et al () reported that tidal flows induce highly nonlinear internal tides in this area. It has also been reported that the intensity of internal tides over the ridge is much higher than it is along the Japanese mainland (Masunaga, Fringer, et al, ; Varlamov et al, ). Varlamov et al () conducted numerical modeling of M 2 internal tides with a horizontal resolution of 1/36° (~3 km), which may not be sufficiently fine to reveal details of the internal tide dynamics, particularly in coastal areas.…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations